Technological Mediation of Document Review : The Use of Textual Replay in Two Organizations - Swarts, Jason (Journal of Business and Technical Communication, 2004)
This article reports findings from a study of writers and reviewers in two complex organizations. The author analyzes the differences between the content, conduct, and resolution of document reviews mediated by hard-copy text and those mediated by textual replay (a series of screen-captured images of the writer’s on-screen writing activity) plus hard-copytext. The results show that reviews mediated by textual replay directed greater attention to issues concerning writing and revision processes. The reviewers offered more tentative revision suggestions and more often enlisted the writers’ participation in articulating, proposing, and implementing the revisions. The article concludes by considering ways that textual replay could be further designed to support the range of joint activities that document review comprises.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMDUwNjUxOTA0MjY0MDM3